The Long-Term Effects of Foetal Life and Birth: A Theoretical Approach - Orosz, Katalin; SNagy, Zita (European Journal of Mental Health, 2018)
A Theoretical Approach: As the first normative crisis, birth might be the primal experience of change for every person. Current research shows that the foetus not only perceives what is happening to him/her in the perinatal period, but he/she even responds to it. Birth experiences and the subsequent reactions create patterns, which may activate again in later life situations. These patterns include physiological, behavioural, cognitive and emotional components, and they influence the personal development as well as the adult functioning and well-being. In this paper, we introduce our theory of the probable long-term effects of perinatal experiences. Our hypotheses are based on medical and epigenetics research findings, on current theories about the significance of the perinatal period and on our 22 years of psychotherapeutic experience. We discuss the effects of the perinatal experiences along the following four topics. According to our assumption, the perinatal experiences become the basic pattern (1) of how we cope with change, (2) of how we manage stress and losses, (3) of how we can bond with others, and (4) of what our attitude is towards touch and towards intimacy. However, the emergence and the functioning of these basic patterns are not rigid and schematic. They are also formed by the subsequent experiences during the entire life, and they can be corrected in any period of life. At the end of the paper we summarise the symptoms in adulthood, when psychotherapy might be recommended to process the traumatic perinatal experiences.